2020
DOI: 10.3390/ijerph17196959
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens: A Bioaugmentation Strategy for Oil-Contaminated and Nutrient-Poor Soil

Abstract: Bioremediation technology is one of the most profitable and sustainable strategies for remediating soils contaminated with hydrocarbons. This study focuses on assessing the influence of biostimulation and bioaugmentation with Pseudomonas fluorescens to contribute to the removal of total petroleum hydrocarbons (TPHs) of a soil. Laboratory studies were carried out (measurements of emitted CO2, surface tension, and residual TPH) to select the best bioaugmentation and biostimulation treatment. The sources of C, N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Some questions remained unanswered in the previous report, such as other genomic mechanisms by which these strains resist pollutants and engage in biodegradative functions, as well as how their biodegradative genes have evolved relative to other pseudomonads. Given that Pseudomonas spp., are well documented to possess a high metabolic activity and potential for hydrocarbon degradation, and can resist a variety of contaminants in diverse environmental habitats [59][60][61], we queried the genomes of the isolated strains in RAST; the total genes for metabolism of aromatic compounds (in parenthesis) are as follows: Pseudomonas alcaligenes OT69 (64), Pseudomonas stutzeri MF28 (77) and Pseudomonas aeruginosa WC55 (153), respectively. We previously reported that P. aeruginosa strain WC55 showed the highest utilization of crude oil in lab-controlled microcosm studies, relative to the other two strains [31], which is consistent with the highest number of xenobiotic genes identified in strain WC55.…”
Section: Xenobiotic Degradation and Speciality Genes In Isolated Strainsmentioning
confidence: 99%
“…Some questions remained unanswered in the previous report, such as other genomic mechanisms by which these strains resist pollutants and engage in biodegradative functions, as well as how their biodegradative genes have evolved relative to other pseudomonads. Given that Pseudomonas spp., are well documented to possess a high metabolic activity and potential for hydrocarbon degradation, and can resist a variety of contaminants in diverse environmental habitats [59][60][61], we queried the genomes of the isolated strains in RAST; the total genes for metabolism of aromatic compounds (in parenthesis) are as follows: Pseudomonas alcaligenes OT69 (64), Pseudomonas stutzeri MF28 (77) and Pseudomonas aeruginosa WC55 (153), respectively. We previously reported that P. aeruginosa strain WC55 showed the highest utilization of crude oil in lab-controlled microcosm studies, relative to the other two strains [31], which is consistent with the highest number of xenobiotic genes identified in strain WC55.…”
Section: Xenobiotic Degradation and Speciality Genes In Isolated Strainsmentioning
confidence: 99%
“…With the combined methods, the acclimatisation of the inoculant might have failed. Thus, much as both biostimulation and bioaugmentation are known to increase the efficiency of soil cleansing processes from oil products, the choice of the appropriate method depends on the environmental conditions as professed by Gutiérrez et al (2020). Taking into account the costly methods of enrichment of the decomposer and their inoculation, we believe that the use of biostimulation in such difficult climatic conditions is the most appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…It grows at temperatures ranging from 4 to 32 • C, with an optimal temperature for growth between 25 and 30 • C. The optimal pH range for growth is 7-8 [51]. Although the application of bacteria from the Pseudomonas fluorescens group in the bioremediation of oil-contaminated soil has not been extensively explored, there are some studies indicating its potential application [52,53].…”
Section: Maldi-tof Analysismentioning
confidence: 99%